Final answer:
To prove m∣ = 180° - m∧4, we use the definition of supplementary angles, which are angles whose measures add up to 180°. Therefore, since m∣ + m∤ = 180°, we can rearrange this to show m∣ = 180° - m∤.
Step-by-step explanation:
The problem stated is: "Given: ∣ and ∤ are supplementary, Prove: m∣ = 180° - m∧4." To prove this, we first need to understand what supplementary angles are. Supplementary angles are two angles whose measures add up to 180°. Therefore, if angles 23 and 24 are supplementary, their measures must add up to 180°. This can be represented as m∣ + m∤ = 180°.
Next, we can manipulate the equation to isolate m∣:
m∣ = 180° - m∤
This is exactly what we were asked to prove. Therefore, the statement m∣ = 180° - m∧4 is proved by understanding the definition of supplementary angles and manipulating the equation that defines them.